Massage therapy as a non-pharmacological analgesia for procedural pain in neonates: A scoping review - Siti Yuyun Rahayu Fitri; Siti Khadijah Nasution; Ikeu Nurhidayah; Nenden Nur Asriyani Maryam (Elsevier, 2021)
Introduction: Neonates who undergo painful medical procedures should be given analgesics to reduce future adverse risks. The evidence for massage therapy (MT) as an analgesic method still varies, both in its terminology and implementation. Only a few studies on this topic have been conducted using a standardised trial approach. This review can thus become the basis for better future research. Objective: This review aims to identify literature on MT practices as a method to manage or control pain in neonates undergoing painful procedures. Methods: The methodology for this review followed the JBI scoping review methodology guidelines. Searches were performed in several databases: MEDLINE (PubMed), CINAHL (EBSCO), Scopus (Elsevier) and EMBASE. Data collected were then extracted by two independent reviewers, synthesised and presented in the form of tables and narratives. Results: Fifteen studies involving a total of 1,058 neonates in nine countries were identified in the search as meeting the criteria set for this review. One study was a comparative study, five were quasi-experiment studies and nine were randomised control trials (RCT). Conclusion: The implementation of massage as a non-pharmacological analgesic method for neonates undergoing painful procedures varied among the reviewed studies. Differences were identified in terms of the body part massaged, the duration and intensity of the massage, the level of pressure and the combination of massage with other methods. All studies presented positive results for reducing pain intensity in neonates undergoing procedural pain. Therefore, it is crucial that the method used for giving massage should be practical, accurate and safe.